Nova espécie de Heleobia (Rissooidea, Hydrobiidae) da planície costeira do sul do Brasil - Silva,Maria Cristina Pons da (2004)
Heleobia robusta, new species from plain coast of Rio Grande do Sul, Brazil, is described. Conchology, conchometry, soft-part morphology including head-food, pallial structures, radula and some aspects of the female and male reproductive systems are provided.